Zum Bekanntheitsgrad erwerbsrelevanter Phraseme des Deutschen. Eine Untersuchung bei Germanistik-Studierenden an der Nationalen Kapodistrias-Universität Athen - Chrissou, Marios; Makos, Evangelos (Linguistik Online, 2018)
It is a common place in the phraseodidactic research that collocational fluency is a significant factor of language fluency. Nevertheless, formulaic language is not focused systematically in the Common European Framework of Reference for Languages and in learning materials for German as a foreign language. The lack of transparency and fragmentary treatment of set phrases have a negative impact over the development of collocational fluency.The present paper focuses on the extent that students of German Language and Literature at the National Kapodistrian University of Athens master high-frequency and common set phrases of German based on a questionnaire survey conducted. The results of the survey are discussed in terms of the deficiencies of institutional guidelines and learning materials. In line with this, proposals are formulated for the improvement of the institutional framework and the teaching of set phrases.